2014
DOI: 10.1200/jco.2013.52.7911
|View full text |Cite
|
Sign up to set email alerts
|

Breast Implant–Associated Anaplastic Large-Cell Lymphoma: Long-Term Follow-Up of 60 Patients

Abstract: Purpose Breast implant–associated anaplastic large-cell lymphoma (ALCL) is a recently described clinicopathologic entity that usually presents as an effusion-associated fibrous capsule surrounding an implant. Less frequently, it presents as a mass. The natural history of this disease and long-term outcomes are unknown. Patients and Methods We reviewed the literature for all published cases of breast implant–associated ALCL from 1997 to December 2012 and contacted corresponding authors to update clinical follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
308
1
17

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 350 publications
(337 citation statements)
references
References 26 publications
4
308
1
17
Order By: Relevance
“…107 In a recent review, no statistical difference was identified between indication for breast-implants (cosmetic vs. reconstructive surgery), laterality and type of implant (saline vs. silicone). 108 The median time to diagnosis of ALCL after implantation was nine years. Patients most often presented with a peri-implant effusion (seroma) or less commonly with a mass adjacent to the effusion.…”
Section: Breast Implant-associated Anaplastic Large-cell Lymphomamentioning
confidence: 99%
See 2 more Smart Citations
“…107 In a recent review, no statistical difference was identified between indication for breast-implants (cosmetic vs. reconstructive surgery), laterality and type of implant (saline vs. silicone). 108 The median time to diagnosis of ALCL after implantation was nine years. Patients most often presented with a peri-implant effusion (seroma) or less commonly with a mass adjacent to the effusion.…”
Section: Breast Implant-associated Anaplastic Large-cell Lymphomamentioning
confidence: 99%
“…Molecular analysis showed clonal TCRG rearrangements in 28 of 29 cases tested. 108 Clinical management was variable and ranged from capsulectomy, mastectomy, radiotherapy, chemotherapy and autologous stem cell transplantation. While median follow-up periods are short (2 years), 93% of patients without a mass had a complete remission compared to 72% of patients with a mass.…”
Section: Breast Implant-associated Anaplastic Large-cell Lymphomamentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of this disease also remains unclear. Miranda et al suggested this is largely attributed to a lack of standardization regarding pathological examination of mammary implants, with the majority of the institutions recommending gross examination alone (5).…”
Section: Discussionmentioning
confidence: 99%
“…34 Although the etiology of this condition is not yet known, it is distinct from systemic ALCL and typically characterized by early detection, an indolent course, and high rates of complete remission after treatment via implant removal and capsulectomy. 35 Cases of BIA-ALCL have been reported across implant types (smooth, textured, saline, silicone), across manufacturers, and in subjects with and without prior implant history; however, more cases have been reported with texturedsurface devices. In the present study, 1 subject in her 10th year of follow-up presented with BIA-ALCL that was detected in seroma fluid.…”
Section: Discussionmentioning
confidence: 99%